Performance study of corncob-fueled updraft gasification with integrated solar power plant as a supporting energy source for the reactor - Rifaldo Pido; Steven Humena; Fadhil Abdullah (National Research and Innovation Agency, 2025)
The increasing demand for energy and the depletion of fossil fuel reserves have accelerated the development of renewable energy sources, with biomass emerging as one of the most promising candidates. Corncobs, an abundant agricultural residue with considerable energy content, represent a viable feedstock for gasification processes. This study evaluates the performance of a corncob-fueled updraft gasifier integrated with a photovoltaic (PV) solar power system as an auxiliary energy source for reactor operation. Experimental tests were conducted to assess flame characteristics, syngas composition, thermal efficiency, and overall energy potential. The influence of air flow rate (AFR) on temperature profiles across the drying, pyrolysis, oxidation, and reduction zones was systematically analyzed. The findings show that low AFR enhances heat accumulation but restricts oxygen supply, whereas excessively high AFR produces cooling effects that reduce thermal efficiency. Optimal operating conditions were achieved at intermediate AFR values (11.5–13.4 m/s), yielding stable heat distribution and high-quality syngas dominated by CO, H₂, and CH₄. Under these conditions, the system demonstrated promising thermal efficiency for small-scale applications. The 600 WP. PV system effectively supplied power to operate the blower, pump, and instrumentation, supporting operational autonomy and reducing reliance on external electricity sources. Overall, the integration of corncob gasification and solar energy offers a sustainable, environmentally friendly, and technically feasible hybrid energy solution, while promoting the utilization of agricultural waste and reducing dependence on fossil fuels in rural areas.